OPTIMALISASI PENGENDALIAN PERSEDIAAN BAHAN BAKU TANDAN BUAH SEGAR (TBS) DALAM PRODUKSI CRUDE PALM OIL (CPO) PADA PKS PT. TUNGGAL YUNUS ESTATE KABUPATEN KAMPAR - Yusup Yusup (STIE Bangkinang Publishing, 2020)
This study aim to determine the optimal inventory control the raw materials of Fresh Fruit Bunches (FFB) in the production of Crude Palm Oil (CPO) at PKS PT. Tunggal Yunus Estate Kampar Regency. The data analysis method used is the EOQ method, the safety stock and the re-order point. Based on the resuts of the analysis, the optimum purchase quantity according to conventional company policy is 321,29 Tons with a purchase frequency of 312 time. Whereas based on the EOQ method the optimum purchase quantity is 658,49 Tons with a purchase frequency of 152 time. Total inventory cost with conventional company pollicy is Rp. 7.676.089 whearese based on the EOQ is Rp. 6.050.243. So by using the EOQ method yhe company can streamline inventory costs by Rp. 1.625.856. meanwhile, for safety inventory and reorder points according to the company policy does not exist, while EOQ method there safety stock is 1,169.38 Tons and r-eorder point is 1,490,67 tons.